New Synthesis Method of Biopolymer Composites Based on Alginate, Carrageenan and ZnONPS for Wound Healing Applications - Mohammed Kassim. Al-Hussainawy; Ali Fahem Getran Khazaali; Makarim A. Mahdi; Waleed K. Abdulsahib; Layth S. Jasim Al-Hayder (Iraqi Journal of Pharmaceutical Sciences, 2024)
Abstract Hydrogels, being a drug delivery system , have great significance, particularly for the topical application in the treatment of open wounds. Their non-adhesiveness, moisture retention, and exudate absorption properties make them ideal for wound healing applications. Using a novel synthesis method, the biomedical hydrogels carrageenan/alginate (κC-Sa) and carrageenan/alginate/ZnO (κC-Sa/ZnO) were synthesized through modified free radical polymerization with acrylic acid as a cross-linker. The hydrogels were characterized using FTIR, FE-SEM, EDX, TEM, and photographic images. κC-Sa and κC-Sa/ZnO were applied as wound healers for injured rats. The synthesized hydrogels have a microstructure, semicrystalline properties, and good ZnO distribution for κC-Sa/ZnO; ZnONPs added to the polymer matrix increased the swelling ratio to 800%. while the water loss percent for κC-Sa is 76% more than κC-Sa/ZnO (70%) in 25 h at room temperature. The hydrogel of κC-Sa/ZnOhows more an antibiotic activity than κC-Sa. The hydrogels were biocompatible when evaluated for their cytotoxic effect using the fibroblast cell line of mice (L929), where κC-Sa/ZnO was more biocompatible than κC-Sa. The κC-Sa/ZnO hydrogel provided more healing than the κC-Sa at 14 days, and this was diagnosed by histological analysis.